Cap-assisted 5-cm diameter cold snare treatment for phytobezoars: A retrospective study - Jie Liu; Zhang Tao; Wenfeng Pu; Yan Zhang; Zonghan Du; Long Chen; Dan Hu; Yanan Chen; Guobin Li; Lisha Zhang; Yiwen Yu; Fuxia Wei (PLoS ONE, 2025)
Background and aims The current treatment options for phytobezoars include endoscopic therapy, chemical lysis, and surgical treatment. These methods are often less efficient or are associated with more adverse events in large-diameter phytobezoars. This study aimed to evaluate the feasibility, effectiveness, and safety of the cap-assisted 5-cm diameter cold snare technique for the treatment of huge phytobezoars. Methods This retrospective study enrolled 24 patients with huge phytobezoars treated with the cap-assisted 5-cm diameter cold snare technique in the Department of Gastroenterology, Nanchong Central Hospital, between December 25, 2022, and October 1, 2023. Patients' clinical characteristics and bezoar features were evaluated, the procedure was recorded, and patients were reviewed and followed with gastroscopy 1 day and 1 month after the procedure. Results Twenty-four patients with huge phytobezoars were treated with the cap-assisted 5-cm diameter cold snare technique during the study period. The median phytobezoar size, break-up time, and extraction time were 5 × 3 cm (range 4–10, 3–5), 10.08 minutes (range 3.31–31.48), and 9.63 minutes (range 6.5–35.71), respectively. All patients achieved satisfactory treatment results, with no residual phytobezoars or gastrointestinal injuries on gastroscopy review 1 day after the procedure, and no postoperative adverse events were found on gastroscopy follow-up 1 month after the procedure. Conclusions The results of this study indicated that the cap-assisted 5-cm diameter cold snare technique is safe, feasible, and effective for treating huge gastric bezoars, offering a new treatment method for this disease. Given the limitations inherent in the retrospective nature and relatively small sample size of this study, a prospective, multicenter, large-sample clinical trial is warranted to evaluate the efficacy and generalizability of this technique comprehensively.